Potato value chain development project in Cameroon. Internal midterm review report - Adamu, I.; Fornkwa, V.; Harahagazwe, D.; Parker, M.; Tiozang, E. (International Potato Center, 2021)
The “ONE WORLD – No Hunger” Initiative (SEWOH) by the German Federal Ministry for Economic Cooperation and Development (BMZ) is part of the G7 goal to free 500 million people from hunger and malnourishment by 2030. SEWOH intends to contribute significantly to reducing poverty and hunger in developing countries in general and Cameroon in particular. The Cameroonian project is part of the framework of the global project – “Green Innovation Centres for the Agriculture and Food Sector” (ProCISA). The project that started in November 2014 is being implemented in close cooperation with the Ministry of Agriculture and Rural Development (MINADER) and the Ministry of Livestock, Fisheries and Animal Industries (MINEPIA), and other partners. It focuses, among others, on the potato value chain to introduce technical and institutional innovations along with the capacity building to increase efficiency and productivity for increased income from potato farming in the West, North-West, and Adamawa regions. With its value chain focus on production and commercialization, ProCISA also targets job creation and the role of women and youth in agriculture and food security. The capacity building around Good Agricultural Practices (GAP) is essential and a significant component in the ProCISA approach. In the implementation of one of its objectives, ProCISA signed a grant agreement with the International Potato Center (CIP) due to its technical expertise on the potato food systems to implement a project titled “Potato Value Chain Development in Cameroon (PVCD),” which started in December 2018. PVCD project built on preliminary interventions conducted by CIP as a consultant from October 2016 to November 2018. In this light, the overall goal of the PVCD project is to promote sustainable intensification of potato production and provide business opportunities for small to medium-sized enterprises through innovative production practices, capacity building, and developing appropriate business models. In a specific manner, the project is structured in five (05) components as follows: Policy engagement and Advocacy (i); Training at scale on good agricultural practices (ii); Seed production and Variety promotion (iii); Promotion of innovations and business models (iv); and M&E and Knowledge sharing (v).